Analysis of squeezing flow of Powell–Eyring fluid with generalized transport phenomena and double stratification past inclined parallel sheets. Issue 6 (2nd November 2022) - Khan, Qaisar; Farooq, Muhammad; Ahmad, Shakeel; Alotaibi, Hammad; Muhammad, Taseer
Abstract : The flow-through stretchable inclined configuration has auspicious utilizes in many engineering and industrial processes, such as extrusion of the molten polymer via converging dies, augmentation of the rate of heat transport in heating processes, injection moulding, cold drawing operation, etc. Owing to these applications, heat transport features in squeezed Powell–Eyring fluid flow passing through the impermeable inclined sheet is scrutinized. The mixed convection phenomenon is also accounted for in flow analysis. The Cattaneo–Christov generalized theories are considered and their heat and mass transport performance is also analyzed. Additionally, characteristics of thermal and solutal stratifications are implemented to elaborate the heat and mass transportations. The strong form of dimensionless coupled equations is evaluated by a homotopic analytical approach with the help of mathematical software 'Mathematica 9'. Graphical distributions are made and debated at distinct physical parameters. Furthermore, drag friction is graphically elaborated. It is noted that decrement occurs in temperature and concentration fields corresponding to higher thermal and solutal relaxation parameters.